Juan Benigno Castañer Moreno, example of doctor and teacher - Tomás de Armas Gil; Yeneisis Herrera Oropesa; Jorge Barroso Cruz; Harold Ricardo Joseph Planas; Ailyn Bárbara Rey Torres; Jorge Fuentes Abreu; Zulimay Torres García; Mara Herrera Almirola; Yadira González Viciedo (Revista Cubana de Medicina Militar)
The trajectory of Colonel (R) Juan Benigno Castañer Moreno, a tireless fighter who has dedicated his life to medicine and the Revolution, is outlined. His investigative work was explored through a documentary review, in his employment record, a search for information available on the internet, his works and an interview carried out by the authors, with which it was possible to specify important passages of such long life. With this work, the authors intend to disseminate the main achievements of Professor Castañer's work, scientific and teaching career as well-deserved recognition of his life's work.